On the need to revise the assessment of qualifications of scientific and pedagogical workers in Russia - Букалерова, Людмила Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Scientific article is devoted to the problems that have arisen in the field of higher education in the Russian Federation in connection with her reforming. Proposed solutions to these problems through the adoption ofclear criteria for the evaluation of teaching and research staff and professional scientific organizations.